1999
DOI: 10.1107/s0907444999006587
|View full text |Cite
|
Sign up to set email alerts
|

Structures of the complexes of peanut lectin with methyl-β-galactose and N-acetyllactosamine and a comparative study of carbohydrate binding in Gal/GalNAc-specific legume lectins

Abstract: The crystal structures of complexes of peanut lectin with methyl-β-galactose and N-acetyllactosamine have been determined at 2.8 and 2.7 Å, respectively. These, and the complexes involving lactose and the T-antigenic disaccharide reported previously, permit a detailed characterization of peanut-lectin–carbohydrate association and the role of water molecules therein. The water molecules in the combining site are substantially conserved in the four complexes. The role of interacting sugar hydroxyl groups, when a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
42
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 54 publications
2
42
0
Order By: Relevance
“…44 Interestingly, as already reported for other carbohydrate-binding proteins, 49 ordered water molecules can be found in the unligated form at positions corresponding to hydroxyl groups in the ligated form (for instance, a water molecule occupies the position of the acetamido carbonyl O in the GalNAc moiety of the T-antigen). In general, water molecules in the carbohydrate-binding region mimic the ligand to a substantial extent not only at the primary site, but also in the regions adjacent to it.…”
Section: Structural Featuresmentioning
confidence: 59%
See 2 more Smart Citations
“…44 Interestingly, as already reported for other carbohydrate-binding proteins, 49 ordered water molecules can be found in the unligated form at positions corresponding to hydroxyl groups in the ligated form (for instance, a water molecule occupies the position of the acetamido carbonyl O in the GalNAc moiety of the T-antigen). In general, water molecules in the carbohydrate-binding region mimic the ligand to a substantial extent not only at the primary site, but also in the regions adjacent to it.…”
Section: Structural Featuresmentioning
confidence: 59%
“…Thus, water plays a significant role in carbohydrate recognition, imparting in some cases exquisite specificity. Comparison of crystal structures of PNA complexed with different ligands (T-antigen, Tant, 43 methyl-b-galactoside, MeGal, 44 N-acetyllactosamine, LacNAc 44 and lactose, Lac 45 ) has shown that water bridges involving water molecules W1 and W2 (Fig. 2) occur in all four complexes.…”
Section: Structural Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Peanut lectin prefers T-antigen (Gal␤1-3GalNAc) to lactose (Gal␤1-4Glc). The 20-fold difference in affinity is attributed to the presence of two water molecules that make hydrogen bonds with the protein and the N-acetyl group of the T-antigen (39,40). In the case of family 15 and 29 carbohydrate-binding modules (CBM15 and -29), the removal of amino acid residues engaging in water-mediated interactions with ligands had comparatively little effect on carbohydrate binding (41,42).…”
Section: Dihedralmentioning
confidence: 99%
“…solution of the complex of PNA with T-antigen confirmed the importance of this residue and revealed the participation of the same water molecule in linking both Leu-212 and Asn-41 to T-antigen (15,17). We extend this study further on the role of Asn-41 in defining the anti-T specificity of PNA more so in relation to the role of the water-mediated hydrogen bond in imparting the lectin its exquisite specificity for the tumorassociated antigen.…”
mentioning
confidence: 96%